Helicopter Ben, monetarism, the New Keynesian credit view and loanable funds - Brett Fiebinger; Marc Lavoie (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
The purpose of this paper is to examine the intellectual roots of monetary dominance; specifically, the view that fiscal policy is largely irrelevant to counter-cyclical macro stabilisation and long-run output growth. A first step towards monetary dominance was the monetarist reinterpretation of the Great Depression. In the 1990s orthodoxy replaced money supply targeting with inflation targeting while preserving monetarist results. In this monetarism without money, fiscal policy was not needed in the short-run for macro stabilisation, and in the long-run could only lead to higher inflation rates and to higher real interest rates that lowered potential output by crowding-out private investment. Expansionary fiscal policy was mostly overlooked in the early 2000s New Keynesian literature on the zero lower bound; instead, the optimism on unconventional monetary policies failed to prepare policymakers for the Global Financial Crisis. The crisis demands far-reaching changes to macro theory not least of which is a recognition that the theory of loanable funds is incapable of providing any insight into how the financial system works in practice or the long-term effects of fiscal policy.
Keywords: B31; E51; E52; E58; 330; quantitative easing; monetarism; bank lending channel; loanable funds